Wind-driven permanent magnet synchronous generators connected to a power grid: Existing perspective and future aspects. Issue 1 (February 2022) - Mahmoud, Mohamed Metwally; Khalid Ratib, Mohamed; Aly, Mohamed M; Abdel-Rahim, Abdel-Moamen M
Scholars are motivated to work in the field of renewable energy systems (RESs) especially on grid-connected wind generators because of the exciting and noticeable developments going on in this area. This progress is utilized to obtain the maximal, efficient, and stable electric power from the RESs and integrating it into existing systems to improve its efficiency, stability, reliability, and overall power quality. Recently, permanent magnet synchronous generators (PMSGs) have become the main pillar of advanced wind systems thanks to their fascinating pluses over other types of wind generators. This paper presents the up-to-date trends in converter topologies, control approaches, maximal power production methods, and grid integration issues for PMSG-based wind systems. The performed statistical analyses assure the dominance of the two-level back-to-back converter among the studied power converter topologies, field-oriented control method for the machine side converter, voltage oriented control method for the grid side converter control, perturb and observe algorithm amongst the studied maximum power point techniques, and fault ride-through capability out of grid integration issues. Further, recent general trends in technological advancements for PMSG wind system components are illustrated as a pie chart in terms of percentage figures. It is expected that the researchers working in this field would benefit from this article in terms of the presented state-of-the-art statistical analyses and its related literature given in this study.